Profiling intercity bus drivers of Malaysia - Bachok, Syahriah; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2018)
This research presents a qualitative research output of a profiling study conducted on intercity bus drivers in Malaysia. Some 1200 respondents were approached at one of the main bus termini in Kuala Lumpur, with a set of questionnaire. The analysis focused on describing and elaborating the socio-demographics characteristics of drivers, their working environment and their perception of the current remuneration systems. Investigating these profiles is important as it will contribute to better understanding of this segment of labour market within the transportation industry as well as the examination of factors contributing to drivers’ behaviour and its relationships with incidents, accidents or road crashes.